Members of the Oral Microbiota Are Associated with IL-8 Release by Gingival Epithelial Cells in Healthy Individuals - Schueller, Katharina; Riva, Alessandra; Pfeiffer, Stefanie; Berry, David; Somoza, Veronika (Frontiers in Microbiology, 2017)
The triggers for the onset of oral diseases are still poorly understood. The aim of this study was to characterize the oral bacterial community in healthy humans and its association with nutrition, oral hygiene habits, and the release of the inflammatory marker IL-8 from gingival epithelial cells (GEC) with and without stimulation by bacterial endotoxins to identify possible indicator operational taxonomic units (OTUs) associated with inflammatory marker status. GECs from 21healthy participants (13 female, 8 male) were incubated with or without addition of bacterial lipopolysaccharides (LPS), and the oral microbiota was profiled using 16S rRNA gene-targeted sequencing. The basal IL-8 release after 6 h was between 9.9 and 98.2 pg/ml, and bacterial communities were characteristic for healthy oral microbiota. The composition of the oral microbiota was associated with basal IL-8 levels, the intake of meat, tea, white wine, sweets and the use of chewing gum, as well as flossing habits, allergies, gender and body mass index (BMI). Additionally, 8 OTUs were associated with high basal levels of IL-8 and GEC response to LPS, with high basal levels of IL-8, and 1 with low basal levels of IL8. The identification of indicator bacteria in healthy subjects with high levels of IL-8 release is of importance as they may be promising early-warning indicators for the possible onset of oral diseases.